Decision-Theoretic Question Generation for Situated Reference Resolution: An Empirical Study and Computational Model. - Gervits, Felix.; Briggs, Gordon.; Roque, Antonio.; Kadomatsu, Genki A.; Thurston, Dean.; Scheutz, Matthias.; Marge, Matthew. (Tufts University. Tisch Library., 2023)
Keywords: human-agent dialogue, reference resolution, situated interaction.; ACM Open.